2020
DOI: 10.21608/svuijas.2020.23456.1003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some natural oils on storage and quality of Balady mandarin fruits

Abstract: This study was conducted during two successive seasons 2017 and 2018 to study the effect of some oils immersing on the storability and quality of Balady mandarin (Citrus reticulate L.) fruits during the storage period. The post-harvest treatments were immersed with camphor oil, linen oil and imazalil either singly or in combination. The fruits were stored at cold condition 8±1°C with 85-90% RH. Samples of each treatment were randomly withdrawn monthly for 4 months. The results showed that fruit weight loss %, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…These results may be due to addition of organic fertilizers, which affect soil properties and improves roots spread and growth, as well as its role in increasing nutrients availability, as well as increasing various activities of microorganisms and their secretions, which may be rich in important growth regulators, and thus improve vegetative growth characteristics and thus influence the fruiting characteristics [20]. These results are consistent with what he found [10], they showed that addition of organic fertilizers increases fruits characteristics of "Sakkoty" date palm trees. Also, these results are consistent with what he found [11 and 12], they showed different pollens sources, had a significant effect on fruit set and fruit yield in date palm trees.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results may be due to addition of organic fertilizers, which affect soil properties and improves roots spread and growth, as well as its role in increasing nutrients availability, as well as increasing various activities of microorganisms and their secretions, which may be rich in important growth regulators, and thus improve vegetative growth characteristics and thus influence the fruiting characteristics [20]. These results are consistent with what he found [10], they showed that addition of organic fertilizers increases fruits characteristics of "Sakkoty" date palm trees. Also, these results are consistent with what he found [11 and 12], they showed different pollens sources, had a significant effect on fruit set and fruit yield in date palm trees.…”
Section: Resultssupporting
confidence: 89%
“…[9] Mentioned that seaweeds extracts and humic acid spray with caused a significant increase in leaves nitrogen, phosphor and potassium compared to unsprayed transplants from his study on Qalib Al-thor mango cultivars. [10] found that organic manure singly or combined with mineral-N and biofertilizers caused significant increases in fruit set and bunch weight for "Sakkoty" date palm trees. Numerous research results conducted in various date palm and date production regions in world indicated that there is a clear effect of source of pollen on percentage of fruit setting, as some researchers found that there are no clear differences in percentage of fruit setting for a specific variety of female date palm as a result of using pollen from different male varieties, while the results of other research indicated that there are clear and statistically significant differences in percentage of fruit setting according to different source of pollen used in pollination.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the fruits treated with Eucalyptus and Clove oils showed a decrease in the percentage of soluble solids content, while the highest values were recorded in the control treatment in both seasons. These results are consistent with those obtained by Amin (2016); El-Shemy (2020) and El-Salhy et al (2020). Similar responses were reported by Saleh et al (2019), who found that essential oils preserved the total soluble solids content.…”
Section: Soluble Solids Content (Ssc %)supporting
confidence: 92%
“…Eucalyptus oil and Clove oil coating guava fruits, in particular, recorded the highest values of firmness compared to other oil treatments in both seasons. Similar results were obtained by Amin (2016); Sebastian et al (2018) and El-Salhy et al (2020). In this study, all tested oils significantly contributed to maintaining the highest fruit firmness of winter guava fruits during the 24-day storage period compared to untreated fruits, with the highest firmness observed in fruits coated with Eucalyptus oil.…”
Section: Fruit Firmness (Newton)supporting
confidence: 90%
See 1 more Smart Citation